Ecotoxicity of the lipid-lowering drug bezafibrate on the bioenergetics and lipid metabolism of the diatom Phaeodactylum tricornutum - Duarte, Bernardo (2019)
Pharmaceutical residues impose a new and emerging threat to the marine environment and its biota. In most countries, ecotoxicity tests are not required for all pharmaceutical residues classes and, even when mandatory, these tests are not performed using marine primary producers such as diatoms. These microalgae are among the most abundant class of primary producers in the marine realm and key players in the marine trophic web. Blood-lipid-lowering agents such as bezafibrate and its derivatives are among the most prescribed drugs and most frequently found human pharmaceuticals in aquatic environments. The present study aims to investigate the bezafibrate ecotoxicity and its effects on primary productivity and lipid metabolism, at environmentally relevant concentrations, using the model diatom Phaeodactylum tricornutum. Under controlled conditions, diatom cultures were exposed to bezafibrate at 0, 3, 6, 30 and 60 μg L-1, representing concentrations that can be found in the vicinity of discharges of wastewater treatment plants. High bezafibrate concentrations increased cell density and are suggested to promote a shift from autotrophic to mixotrophic metabolism, with diatoms using light energy generated redox potential to breakdown bezafibrate as carbon source. This was supported by an evident increase in cell density coupled with an impairment of the thylakoid electron transport and consequent photosynthetic activity reduction. In agreement, the concentrations of plastidial marker fatty acids showed negative correlations and Canonical Analysis of Principal coordinates of the relative abundances of fatty acid and photochemical data allowed the separation of controls and cells exposed to bezafibrate with high classification efficiency, namely for photochemical traits, suggesting their validity as suitable biomarkers of bezafibrate exposure. Further evaluations of the occurrence of a metabolic shift in diatoms due to exposure to bezafibrate is paramount, as ultimately it may reduce O2 generation and CO2 fixation in aquatic ecosystems with ensuing consequences for neighboring heterotrophic organisms.